Development of E-Module Materials of Quantities and Units Using Canva to Increase Students' Interest in Learning - Wulandari, Dinda; Risdianto, Eko; Setiawan, Iwan (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2022)
This study aims to determine the characteristics and feasibility of developing an e-module using the Canva application to increase the learning interest of high school students. This research is a follow-up research that has been done previously which is only limited to the analysis stage, this research uses the ADDIE model RnD method. But in this research, it is only up to the development stage. This study uses an expert validation sheet assessment instrument that contains aspects of material, language and media. Based on the results of product validation tests that were validated by experts so that the percentage score for the material aspect was 85.45%, language was 87.50%, media was 89.58%, and interest in learning was 90.63%. The final result of the average score is 88.28%, can be categorized as very valid and the results of the student's perception response show very well with a percentage of 86.23%. Therefore, the e-module material of magnitude and unit using Canva to increase the learning interest of high school students is declared as a product that is feasible to use.